Nucleotide sequence of a citrate utilization gene from Citrobacter amalonaticus. - Daimon, H (1989)
The chromosomal DNA fragment (BamHI-BglII fragment of 2,972 base pairs) conferring citrate utilization in Citrobacter amalonaticus ATCC 25405 was cloned and sequenced. Two genes (citA and citB) identified in the Cit+ determinant were found in a BamHI-BglII fragment from C. amalonaticus. Southern DNA-DNA hybridization experiments and the construction of Cit- mutants of C. amalonaticus showed that C. amalonaticus has a single copy of the cit gene on the chromosome.